2009
DOI: 10.1016/j.vetmic.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of bovine norovirus infection by RT-PCR and a VLP-based antibody ELISA

Abstract: genotype 2 bovine noroviruses rose in the first 6 months of life and were maintained in adults. 29Together the results of virus prevalence and seroprevalence studies suggest that bovine 30 norovirus infection occurs early in life and that re-infection with serologically related bovine 31 noroviruses strains could occur in adult cattle as reported for rotaviruses. The antibody rise 32 against genotype 2 bovine noroviruses in the adult cattle also suggests a short lived and/or 33 strain specific immunity as alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 31 publications
3
33
2
6
Order By: Relevance
“…Twenty-one of 101 (20.8 per cent) samples were positive for bovine norovirus, indicating that norovirus and rotavirus may cause a simultaneous infection. The norovirus detection rate (21 per cent) observed in this study is higher than that observed in a previous survey conducted in asymptomatic animals in Italy (data not shown), and in other surveys conducted in Europe (van der Poel and others 2003, Mauroy and others 2009, Reuter and others 2009, Mijovski and others 2010). However, it must be considered that only a cohort of diarrhoeic calves was examined out of the total number of animals presented at the diagnostic facilities.…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…Twenty-one of 101 (20.8 per cent) samples were positive for bovine norovirus, indicating that norovirus and rotavirus may cause a simultaneous infection. The norovirus detection rate (21 per cent) observed in this study is higher than that observed in a previous survey conducted in asymptomatic animals in Italy (data not shown), and in other surveys conducted in Europe (van der Poel and others 2003, Mauroy and others 2009, Reuter and others 2009, Mijovski and others 2010). However, it must be considered that only a cohort of diarrhoeic calves was examined out of the total number of animals presented at the diagnostic facilities.…”
contrasting
confidence: 82%
“…Interestingly, the situation described in Italy is quite similar to a recent report from Hungary, where both GIII.1 and GIII.2 were also identified. Another study conducted in Europe reported only GIII.2 (Mauroy and others 2009), suggesting that this strain was the predominant norovirus responsible for infection in cattle (Scipioni and others 2008). Conversely, in Italy different bovine norovirus strains appear to circulate simultaneously, and are likely to infect farmed cattle at a high rate.…”
mentioning
confidence: 99%
“…To our knowledge, no previous studies investigated the presence of BoNoV in environmental water sources. However, several studies have investigated BoNoV in fecal samples from both asymptomatic and diarrheic bovine (18,29,30). In the present study, BoNoV was detected in 2 of 11 SW samples.…”
Section: Real-time Pcr and Rt-pcr Analysesmentioning
confidence: 51%
“…BoNoVs have been detected using molecular methods in faecal samples of diarrhoeic calves, either alone or as co-infections with other enteric viruses, such as rotavirus, nebovirus, coronavirus and bovine viral diarrhoea virus (BVDV) (Smiley et al, 2003;Park et al, 2007;Mauroy et al, 2009a;Jor et al, 2010;Di Bartolo et al, 2011;Cho et al, 2013). It is possible that mixed infections influence the severity of BoNoV infections.…”
Section: Pathogenesis and Clinical Features Of Bovine Norovirus Infecmentioning
confidence: 99%